Phytochemicals of Euphorbia hirta L. and Their Inhibitory Potential Against SARS-CoV-2 Main Protease - Cayona, Ruel; Creencia, Evelyn (Frontiers in Molecular Biosciences, 2022)
Euphorbia hirta L. is a medicinal plant widely used in the Philippines and across tropical Asia against various diseases and including respiratory disorders. In this study the phytochemical components of E. hirta were investigated in sillico for their potential to inhibit the severe acute respiratory syndrome-coronavius-2 main protease (SARS-CoV-2 Mpro), a coronavirus disease 2019 (COVID-19) drug target that plays a critical role in the infection process by SARS-CoV-2. Phytochemical mining in tandem with virtual screening (PM-VS) was the strategy implemented in this study which allows efficient preliminary in silico assessment of the COVID-19 therapeutic potential of the reported phytochemicals from the plant. The main rationale for considering E. hirta in the investigation was its reported efficacy against respiratory disorders. It is very promising to investigate the phytochemicals of E. hirta for their potential efficacy against the disease as COVID-19 that also targets the respiratory system. A total of 298 E. hirta phytochemicals were comprehensively collected from the scientific literature. One hundred seventy (170) of these phytochemicals were computed through molecular docking to have comparable or better binding properties (promising inhibitors) toward SARS-CoV-2 Mpro than known in vitro inhibitors. In connection to our previous work considering different medicinal plants, antiviral compounds were also rediscovered from the phytochemical composition of E. hirta. This finding provides additional basis for the potential of the plant (or its phytochemicals) as COVID-19 therapeutic directly targeting drug targets as SARS-CoV-2 Mpro and/or addressing respiratory system-related symptoms. The study also highlights the utility of PM-VS which can be efficiently implemented in the preliminary steps of drug discovery and development.